Queer liveability: Inclusive church-scenes. (September 2019) - Cuthbert, Karen; Taylor, Yvette
This article explores queer religious youths' engagement with the Metropolitan Community Church (MCC) – a church founded as a space of worship for LGBT Christians. Interested in sources of well-being in queer people's lives, we show how MCC provided young religious queer people with a sense of home, family, and a phenomenological experience of 'fit' and 'ease'. We connect to literature on the subjectivization of religion and suggest that MCC is a significant actor in this process, with spatial and liturgical practices that encourage the development of one's own spiritual journey. However, we also temper these claims by showing how 'tradition' was still valued by many participants, evidenced in their continued affiliation with other (often non-inclusive) churches. We argue that this complicates arguments regarding 'inclusivity' as these 'non-inclusive' churches could also provide spaces of succour and support. Finally, we also consider MCC's relationship with queerness/LGBT: participants differed in whether or not they saw MCC as part of or apart from the 'scene', complicating questions raised about assimilation vs. separatism, with the relative weight of 'LGBT' and 'Christian'.